The balancing of empowerment. A strategic resource based model of organizing innovation activities in service and low-tech firms - Sundbo, Jon
The writer focuses on balancing the empowerment of employees to promote corporate entrepreneurship with appropriate control measures. Networking and the empowerment of customers are felt to be under utilized, whilst strategy and a linear organization of innovation are considered most important as control mechanisms.
The empowerment of employees as corporate entrepreneurs in the innovation process is important. However, it is also important to control, and thus balance it. This article tries to answer two questions : Do firms stimulate and balance innovation empowerment, and, if so, how do they organize and manage it? First, innovation empowerment is discussed theoretically within the framework of the resource based theory of the firm. Firms might establish two systems of organizing innovation activities. One is the expert system (typically R&D departments), the other is the empowerment system. The empowerment system is particularly important for low-tech and service firms. The empowerment system is organized corporate entrepreneurship which is controlled by the management-in contrast to free (uncontrolled) corporate entrepreneurship. The argument for controlling empowerment is that it may easily use too many resources. Second, the two questions are discussed empirically on the basis of case studies in Danish firms. Nearly all firms practised empowerment stimulation. A fewer, but still most, practised empowerment control. Inducement mechanisms which stimulate the empowerment and control mechanisms were found. Strategy, particular innovation departments and practical instruments for procuring ideas were the most important inducement mechanisms. Networking and empowerment of customers were under-utilized mechanisms. The most important control mechanisms were the strategy and a linear organization of the innovation process. Organizational learning is the most efficient control mechanism, but is difficult to practice. A model of the balance system is put forward.
Keywords: Empowerment